2018
DOI: 10.1093/toxsci/kfy083
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nicotine Exposure Leads to Augmented Expression of the Antioxidant Adipose Tissue Triglyceride Lipase Long-Term in the White Adipose of Female Rat Offspring

Abstract: Globally, approximately 10%-25% of women smoke during pregnancy. Since nicotine is highly addictive, women may use nicotine-containing products like nicotine replacement therapies for smoking cessation, but the long-term consequences of early life exposure to nicotine remain poorly defined. Our laboratory has previously demonstrated that maternal nicotine exposed (MNE) rat offspring exhibit hypertriglyceridemia due to increased hepatic de novo lipogenesis. Hypertriglyceridemia may also be attributed to impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The recorded weight gain indicated that the 2.5%-nicotine-exposed group exhibited the most significant gain in body weight from the beginning to the end of adolescence. Accumulating evidence has linked prenatal nicotine exposure and obesity later in life [33][34][35]. Clinical settings have revealed that prenatal exposure to traditional nicotine is associated with increased weight gain during adolescence, including subcutaneous and intra-abdominal fat [36].…”
Section: Discussionmentioning
confidence: 99%
“…The recorded weight gain indicated that the 2.5%-nicotine-exposed group exhibited the most significant gain in body weight from the beginning to the end of adolescence. Accumulating evidence has linked prenatal nicotine exposure and obesity later in life [33][34][35]. Clinical settings have revealed that prenatal exposure to traditional nicotine is associated with increased weight gain during adolescence, including subcutaneous and intra-abdominal fat [36].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, protein-restricted rat offspring show increased antioxidant abundance in skeletal muscle, concomitant with altered activity of aerobic metabolism enzymes [62]. Gestational exposure to nicotine has been found to elicit similar effects in adipose tissue at three weeks and six months of age, as SOD1 and SOD2 protein levels were 37-48% higher in the white adipose tissue of IUGR offspring compared to control offspring [63]. While the increase in antioxidant abundance is thought to occur as a compensatory mechanism in response to oxidative stress, it has also been proposed that inflammation may have a contributing role in this process [62,63].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Interestingly, protein-restricted rat offspring show increased antioxidant abundance in skeletal muscle, concomitant with altered activity of aerobic metabolism enzymes [63]. Gestational exposure to nicotine has been found to elicit similar effects in adipose tissue at three weeks and six months of age, as SOD1 and SOD2 protein levels were 37-48% higher in the white adipose tissue of IUGR offspring compared to control offspring [64]. While the increase in antioxidant abundance is thought to occur as a compensatory mechanism in response to oxidative stress, it has also been proposed that inflammation may have a contributing role in this process [63,64].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%